Analisis dan Optimalisasi Proses Bisnis LPPM Universitas Swasta di Jakarta melalui Pendekatan IDEF0 - Silitonga, Riana Magdalena; Sukwadi, Ronald; Bangnga, Hedwig Eryn Sua; Thu, Nguyen Thi Bich (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2025)
The business process improvement at the Research and Community Services Center (LPPM), at a private university in Jakarta, was initiated due to unclear Standard Operating Procedures (SOPs) and the introduction of a new operational mechanism. The main objective of this research is to analyze and map the current business processes to clarify existing workflows. The IDEF0 method is used to identify and evaluate these processes, while the overall analysis follows Business Process Improvement (BPI) principles. The focus is on three core processes: proposal submission, fund disbursement, and reporting—each essential to research, community service, and publication activities. Improvements are proposed through the development of a revised SOP and the design of an online database system. These enhancements are based on interviews with key stakeholders, including the Head of the Center for System Development, LPPM officials, and staff. The use of the IDEF0 method significantly assists in identifying the roles and responsibilities of involved parties in each process. It provides a structured approach to evaluating and refining workflows. As a result, a new database system is being designed to support better data management and documentation at LPPM. This system will be built upon the improved processes identified through the IDEF0 analysis, ensuring more efficient and transparent operations.